1997
DOI: 10.1136/gut.41.2.229
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyltransferase 2 genotype in colorectal cancer and selective gene retention in cancers with chromosome 8p deletions

Abstract: Background-Genetic polymorphisms in N-acetyltransferase (NAT2) can change the normally fast acetylation of substrates to slow acetylation, and have been associated with the development of some cancers. The NAT2 locus may also suVer dysregulation during cancer progression, as the gene resides on chromosome 8p22, a region which is frequently deleted in colorectal cancer. Subjects and Methods-A polymerase chain reaction based method was used to determine NAT2 genotype in 275 patients with colon cancer and 343 nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
1
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 33 publications
1
25
1
1
Order By: Relevance
“…The polymorphic status of the N-acetyltransferase 2 gene in these cancer and control groups was determined previously (Hubbard et al, 1997 …”
Section: Materials and Methods Study Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…The polymorphic status of the N-acetyltransferase 2 gene in these cancer and control groups was determined previously (Hubbard et al, 1997 …”
Section: Materials and Methods Study Casesmentioning
confidence: 99%
“…Polymorphisms of NAT2 that result in slow acetylation of metabolites have been associated with bladder cancer (Risch et al, 1995) and, conversely, fast acetylators may be more common in colorectal cancer and some types of breast cancer (Lang et al, 1986;Agundez et al, 1995). However these associations are weak and are not supported by all studies (Bell et al, 1995a;Hubbard et al, 1997).A potentially confounding factor in these assessments is the contribution of NATI, a closely related enzyme that shares some substrate specificity with NAT2 (Hein et al, 1992), which is expressed at higher levels than NAT2 in colonic epithelial cells (Turesky et al, 1991). Recent studies have shown that NATI is also polymorphic and 15 variants have been detected in animal and human gene sequences Weber and Vatsis, 1993;Grant et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed only one study involvin2 allelic loss of NAT2 has been published. and it was performed in colon cancer (Hubbard et al 1997). …”
mentioning
confidence: 99%
“…However, results from a number of studies show only weak and inconsistent associations with disease susceptibility. N-acetyltransferase 2 (NAT-2) polymorphism may be implicated in susceptibility to colon cancer (Lang et al, 1986;Wohlleb et al, 1990;Illett et al, 1994;Probst-Hensch et al, 1995), but there is evidence that its relationship may be by linkage with other genes rather than causally (Hubbard et al, 1997).We have used a polymerase chain reaction (PCR) strategy to investigate whether polymorphisms in the microsomal epoxide hydrolase gene (mEPHX) (Hassett et al, 1994) have any relationship to colon cancer. The enzyme is expressed in many tissues, including colon and liver.…”
mentioning
confidence: 99%